Loan loss provision behavior in China Banking system from 2009 to 2014 - He, Junnan (2016)
The purposes of this paper are to investigate the loan loss provision behavior in China’s banks from 2009 to 2014. This study is based on relevant empirical literatures and 36 commercial banks in China. Two model are used in this research, which is Stochastic frontier analysis and Generalized method of moments. X-efficiency is included in this study and the estimation variables of loan loss provision are estimated by GMM model. The results in this research strongly support the capital management and earning management hypotheses in China banking system. However, there is no significant variable supporting a pro-cyclical provision behavior in China banking system.